Virtual student experiences: A case study of objectives, outcomes, and anticipated consequences. Issue 3 (9th March 2021) - Shappell, Eric; Egan, Daniel J.; Eyre, Andrew; Nadel, Eric; Wittels, Kathleen
Abstract: Due to the COVID‐19 pandemic, most in‐person visiting clerkship opportunities have been canceled. Many institutions have developed virtual experiences to fill this void; however, the format and objectives of these experiences are variable. This article describes an education intervention for visiting students where both learner‐oriented and program‐oriented outcomes of a nonclerkship virtual student experience are explored. This intervention consisted of five 1‐hour case‐based teaching sessions in addition to attendance at weekly residency conference over a 1‐week period. The primary outcomes were student ratings of how the experience impacted their 1) perception of the program's educational environment and culture, 2) medical knowledge, and 3) program ranking before and after the experience. Of 24 participants, 15 students (63%) completed the final evaluation, all with positive summative rankings in every domain measured. Of the 15 respondents, 12 (80%) reported an increase in where they would rank the program after the experience compared to before, and nine of 15 (60%) stated that they would rank the program #1 if making a list at the time they completed the final evaluation. Future study should examine long‐term outcomes of these interventions including decisions regarding where students apply, who programs interview, and ranking decisions of students and programs.